Serotonin Syndrome Caused by Fentanyl and Methadone in a Burn Injury. Issue 1 (23rd January 2015) - Hillman, Ashley D.; Witenko, Corey J.; Sultan, Said M.; Gala, Gary
<x xml:space="preserve">Abstract</x> Serotonin syndrome is a syndrome identified by a triad of altered mental status, neuromuscular overactivity, and autonomic instability caused by the overstimulation of serotonin in the central nervous system and periphery. Serotonin syndrome may be provoked with the addition or increase in serotonergic agents such as selective serotonin reuptake inhibitors, serotonin norepinephrine reuptake inhibitors, tricyclic antidepressants, and monoamine oxidase inhibitors as well as other agents with serotonergic properties. Some narcotics, including fentanyl and methadone, have these properties and may be associated with the development of serotonin syndrome when used in conjunction with other agents. Currently, there are no identified case reports of narcotics as the sole agent causing serotonin syndrome. This report provides a brief overview of serotonin syndrome, particularly with cases involving administration of narcotics such as fentanyl and methadone. The case described is the first report associated with fentanyl and methadone without the coadministration of other serotonergic agents, and a possible drug interaction with voriconazole is discussed. This raises awareness of using multiple serotonergic narcotics and the potential precipitation of serotonin syndrome.